Comparative study of akidah akhlak learning achievement between special and regular class viii students at madrasah tsanawiyah muhammadiyah batur - Nada Rihadatul Aisy Allaily; Isfihani; Iffah Mukhlisah; Ahmad Najamuddin (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
Education is a crucial factor in a country's progress and a fundamental right of every citizen. It helps individuals develop intellectual, emotional, and spiritual intelligence while shaping their personality and maturity. In accordance with Law No. 2 of 1989, education aims to enhance the quality of human resources through learning that encompasses cognitive, affective, and psychomotor aspects. Islam also emphasizes the importance of seeking knowledge, as stated in the Qur'an and Hadith. Education is not only intended to improve academic achievement but also to cultivate good morals. At Madrasah Tsanawiyah Muhammadiyah Batur Banjarnegara, the Merdeka Curriculum is implemented in two programs: a special program focusing on Quran memorization and a regular program emphasizing academics. The special program includes additional curriculum content, but the heavier workload may hinder students' focus. The effectiveness of this additional curriculum still needs evaluation to better meet students' needs. The Akidah Akhlak education at the madrasah aims to instill religious values and shape students' character. In terms of academic achievement, the learning approach in the special and regular programs impacts students' performance differently. Students in the special program tend to excel due to more intensive academic support, while students in the regular program often face challenges in achieving optimal academic performance. This study aims to analyze the academic achievement of eighth-grade students in Akidah Akhlak at Madrasah Tsanawiyah Muhammadiyah Batur, Banjarnegara Regency, in the 2024/2025 academic year, both in the special and regular programs, and to compare the differences in academic achievement between the two programs. The research adopts a quantitative approach with a descriptive comparative research design. The population consists of 109 students, and the sample is selected using proportionate stratified random sampling, resulting in 46 students. Data collection methods include observation and documentation. Data analysis is conducted using statistical hypothesis testing with an independent sample t-test. Based on the analysis results, the following conclusions are drawn: 1) The academic achievement of eighth-grade students in the special program at Madrasah Tsanawiyah Muhammadiyah Batur, Banjarnegara Regency, shows that 13% (3 students) fall into the good category, 74% (17 students) in the fair category, and 13% (3 students) in the poor category. Thus, most students in the special program fall into the fair category, with an average score of 61.34, rounded to 61. 2) The academic achievement of eighth-grade students in the regular program shows that 17.3% (4 students) are in the good category, 56.6% (13 students) in the fair category, and 26.1% (6 students) in the poor category. Thus, most students in the regular program fall into the fair category, with an average score of 57.8, rounded to 58. 3) There is no significant difference in academic achievement between eighth-grade students in the special and regular programs at Madrasah Tsanawiyah Muhammadiyah Batur, Banjarnegara Regency, in the 2024/2025 academic year. This conclusion is based on hypothesis testing, which, at a 5% significance level, accepts H0 and rejects Ha. This is evidenced by the independent t-test, where the calculated t-value is 1.480 and the critical t-value is 2.014 (1.480 < 2.014).